Good Bye Rush Hour Trains, Hello Morning Walks. Changes in Morning Experience for Japanese Retirees - Yohko Tsuji (lo Squaderno, 2014)
Morning is the "junction between nighttime and daytime" when most people experience the transition from restful sleep to actions. It comes every day with the light dispelling the darkness and human motions and bird chirpings breaking the stillness of the night. While the morning thus described is repeated day after day, people’s experiences of it may change drastically when they retire. In this article, I will examine such changes in morning experiences among Japanese retirees who live in a suburb of Osaka, Japan’s second largest city, and who worked in the metropolis before retirement.